Prevalence of non-alcoholic fatty liver disease among inflammatory bowel disease patients: a systematic review and meta-analysis - Zhao, Yuyang; Wang, Jiangbin; Sun, He (Frontiers in Medicine, 2025)
BackgroundRecent studies suggest that individuals with inflammatory bowel disease (IBD) are at a significantly higher risk of developing non-alcoholic fatty liver disease (NAFLD) compared to the general populace. Furthermore, the coexistence of NAFLD is likely to intensify the overall health impact experienced by individuals with IBD.MethodsThis review aims to assess the prevalence of NAFLD and its associated risk factors in IBD patients through systematic analysis. We searched for relevant literature in the PubMed and Medline databases from January 2014 to April 2024 and conducted a meta-analysis to quantitatively synthesize eligible studies, the search criteria were designed to encompass a broad spectrum of research investigating the link between IBD and NAFLD. After completing the literature search, a meticulous screening process was undertaken to filter out studies that did not meet the predefined eligibility criteria.ResultsThe analysis encompassed 26 studies, representing a cohort of over 429,550 IBD patients. Our study indicated that the aggregate incidence of NAFLD within this IBD population was 34%, with a 95% confidence interval ranging from 27% to 41%. Additionally, the research highlighted that the likelihood of NAFLD onset is increased in IBD patients with a prolonged illness duration, obesity, and those presenting metabolic syndrome characteristics.ConclusionThe incidence of NAFLD among individuals with IBD notably exceeds that observed in the general populace. This heightened prevalence correlates with factors such as disease severity, metabolic risk profiles, and the impact of pharmacological interventions. Further research is needed to further elucidate these risk factors and establish screening recommendations.